Recent advances in PVP-assisted thermal treatment: Impact on nanostructure properties, potential applications, challenges, and future perspectives - Al-Hada N.M.; Xu S.; Al-Ghaili A.M.; Ali Al-Asbahi B.; Baqiah H.; Yang J.; Azlan M.N.; Li Q. (Elsevier B.V., 2025)
Nanotechnology has garnered significant attention for its wide-ranging applications in biomedicine, energy, and environmental science. The synthesis of nanomaterials with specific properties is crucial for advancing these fields. Among various methods, thermal treatment has emerged as a promising technique for producing diverse nanostructures. However, thermal treatment alone often leads to larger particle sizes and poor uniformity, limiting the practical applications of the resulting nanomaterials. Incorporating polyvinylpyrrolidone (PVP) as a capping agent addresses these challenges by reducing particle size and enhancing uniformity. Optimizing parameters such as PVP concentration, molecular weight, temperature, and precursor ratios is key to improving the performance of the PVP-assisted thermal treatment method. This paper reviews recent progress in synthesizing nanostructures using PVP-assisted thermal treatment, including key characterization techniques. It also examines the applications of these nanostructures in fields such as biomedicine, energy, and environmental science. The review identifies challenges in the synthesis and characterization process, while also outlining potential future directions for enhancing this method. The insights provided will be valuable to researchers working in nanotechnology and related disciplines. ? 2024 The Author(s)